Rancang Bangun (SHANTI) Smart Hotspot Fakultas Teknologi Informasi dan Sains Universitas Hindu Indonesia Menggunakan Mikrotik dan Mikhmon - Mertha, I Made Buana; Dewi, Ida Ayu Utari; Wardana, I Putu Mahendra Adi (RESI : Jurnal Riset Sistem Informasi, 2025)
Internet connectivity has become an essential need in various contexts, including the campus environment. The Faculty of Information Technology and Science at Hindu University of Indonesia plays a central role as an educational institution that focuses on information technology, making the use of information technology and the internet increasingly crucial in supporting the learning process and administrative activities. The research carried out by researchers to overcome these challenges requires efforts to optimize the use of the MikroTik hotspot network so that it becomes more effective and efficient in the academic environment. Therefore, researchers will design (shanti) smart hotspots, Faculty of Information Technology and Science, Indonesian Hindu University using MikroTik and Mikhmon, by implementing stricter control measures that can be implemented to avoid misuse of internet access, while increasing overall network security in the area faculty environment